Collection of SARS-CoV-2 Virus from the Air of a Clinic within a University Student Health Care Center and Analyses of the Viral Genomic Sequence - Lednicky, John A.; Shankar, Sripriya N.; Elbadry, Maha A.; Gibson, Julia C.; Alam, Md. Mahbubul; Stephenson, Caroline J.; Eiguren-Fernandez, Arantzazu; Morris, J. Glenn; Mavian, Carla N.; Salemi, Marco; Clugston, James R.; Wu, Chang-Yu (Aerosol and air quality research, 2020)
The progression of COVID-19 worldwide can be tracked by identifying mutations within the genomic sequence of SARS-CoV-2 that occur as a function of time. Such efforts currently rely on sequencing the genome of SARS-CoV-2 in patient specimens (direct sequencing) or of virus isolated from patient specimens in cell cultures. A pilot SARS-CoV-2 air sampling study conducted at a clinic within a university student health care center detected the virus vRNA, with an estimated concentration of 0.87 virus genomes L −1 air. To determine whether the virus detected was viable (‘live’), attempts were made to isolate the virus in cell cultures. Virus-induced cytopathic effects (CPE) were observed within two days post-inoculation of Vero E6 cells with collection media from air samples; however, rtRT-PCR tests for SARS-CoV-2 vRNA from cell culture were negative. Instead, three other fast-growing human respiratory viruses were isolated and subsequently identified, illustrating the challenge in isolating SARS-CoV-2 when multiple viruses are present in a test sample. The complete SAR-CoV-2 genomic sequence was nevertheless determined by Sanger sequencing and most closely resembles SARS-CoV-2 genomes previously described in Georgia, USA. Results of this study illustrate the feasibility of tracking progression of the COVID-19 pandemic using environmental aerosol samples instead of human specimens. Collection of a positive sample from a distance more than 2 m away from the nearest patient traffic implies the virus was in an aerosol.